An anti-inflammatory and anti-fibrotic proprietary Chinese medicine nasal spray designated as Allergic Rhinitis Nose Drops (ARND) with potential to prevent SARS-CoV-2 coronavirus infection by targeting RBD (Delta)- angiotensin converting enzyme 2 (ACE2) binding - Ka Man Yip; Kwan Ming Lee; Tzi Bun Ng; Shujun Xu; Ken Kin Lam Yung; Shaogang Qu; Allen Ka Loon Cheung; Stephen Cho Wing Sze (BMC, 2022)
Abstract Background Since the outbreak of COVID-19 has resulted in over 313,000,000 confirmed cases of infection and over 5,500,000 deaths, substantial research work has been conducted to discover agents/ vaccines against COVID-19. Undesired adverse effects were observed in clinical practice and common vaccines do not protect the nasal tissue. An increasing volume of direct evidence based on clinical studies of traditional Chinese medicines (TCM) in the treatment of COVID-19 has been reported. However, the safe anti-inflammatory and anti-fibrotic proprietary Chinese medicines nasal spray, designated as Allergic Rhinitis Nose Drops (ARND), and its potential of re-purposing for suppressing viral infection via SARS-CoV-2 RBD (Delta)- angiotensin converting enzyme 2 (ACE2) binding have not been elucidated. Purpose To characterize ARND as a potential SARS-CoV-2 entry inhibitor for its possible preventive application in anti-virus hygienic agent. Methods Network pharmacology analysis of ARND was adopted to asacertain gene targets which were commonly affected by COVID-19. The inhibitory effect of ARND on viral infection was determined by an in vitro pseudovirus assay. Furthermore, ARND was confirmed to have a strong binding affinity with ACE2 and SARS-CoV-2 spike-RBD (Delta) by ELISA. Finally, inflammatory and fibrotic cell models were used in conjunction in this study. Results The results suggested ARND not only inhibited pseudovirus infection and undermined the binding affinity between ACE2 and the Spike protein (Delta), but also attenuated the inflammatory response upon infection and may lead to a better prognosis with a lower risk of pulmonary fibrosis. The data in this study also provide a basis for further development of ARND as an antiviral hygienic product and further investigations on ARND in the live virus, in vivo and COVID-19 patients. ARND holds promise for use in the current COVID-19 outbreak as well as in future pandemics. Conclusion ARND could be considered as a safe anti-SARS-CoV-2 agent with potential to prevent SARS-CoV-2 coronavirus infection. Graphical abstract